DDX60 Is Associated With Glioma Malignancy and Serves as a Potential Immunotherapy Biomarker - Zhang, Jingwen; Fu, Minjie; Zhang, Mengli; Zhang, Jinsen; Du, Zunguo; Zhang, Hongyi; Hua, Wei; Mao, Ying (Frontiers in Oncology, 2021)
Abstract DDX60, an interferon (IFN)-inducible gene, plays a promotional role in many tumors. However, its function in glioma remains unknown. In this study, bioinformatic analysis (TCGA, CGGA, Rembrandt) illustrated the upregulation and prognostic value of DDX60 in gliomas. Immunohistochemical staining of clinical samples (n=49) validated the DDX60 expression is higher in gliomas than in normal tissue (n=20, P<0.0001). It also could be included in nomogram as a parameter to predict the 3-and 5-years survival risk (C-index=0.86). The biological process of DDX60 in glioma was mainly enriched in the inflammatory and immune response by GSEA and GO analysis. DDX60 expression had a positive association with most inflammatory-related functions, such as hematopoietic cell kinase (HCK) (R=0.31), interferon (R=0.72), STAT1 (R=54), and a negative correlation with IgG (R=-0.24). Furthermore, DDX60 expression tends to be positively related to multiple infiltrating immune cells, while negatively related to CD56 dim nature killer cell in glioma. Some important immune checkpoints, like CTLA-4, PD-L1, EGF, CD96, and CD226, were all positively related with DDX60 (all pearson correlation R> 0.26). The expression and correlation between DDX60, EGF and PD-L1 was confirmed by western blot in clinical samples (n=14, P<0.0001). These results indicated that DDX60 might has important clinical significance in glioma and could serve as a potential immune therapeutic target.